A eficiência de mercado a partir da econofísica: uma análise da relação do expoente de hurst com a incerteza política econômica e controle estatal - ALMEIDA, Dinah Costa (2023)
The present work has as main objective to analyze how certain factors, such as: economic political uncertainty and state control, influence the variation of market inefficiency levels through the predictability of return of financial assets of publicly traded Brazilian companies. The research is based on the Efficient Market Hypothesis (HME), and presents in its content a brief introduction to Econophysics. The research utilizes physical concepts involving random walk analysis and mathematical and statistical devices such as the Hurst Exponent. To perform this study, 135 Brazilian listed companies were selected, whose data refer to shares traded on B3 between 2010 and 2018. To obtain the results, the Data Regression method was used. in Dashboard through Pooled Data. In general, the results indicate that: in periods of economic political uncertainty, companies have less inefficiency in their securities; companies under state control tend to be more inefficient in their securities. The findings are relevant for providing information that helps in understanding the efficiency in predicting return on securities traded in the Brazilian capital markets.